ANALYSIS OF TEACHER ACTIVITY CENTERS AND TEACHER PERFORMANCE ASSESSMENT OF PRINCIPALS' MANAGERIAL CAPACITY THROUGH COMPETENCE PROFESSIONALISM AS AN INTERVENING VARIABLE AT SMAN 1 THE MAIN SHIA OF BENER MERIAH REGENCY - Paridah; Elfitra Desy Surya; Mesra B (RADJA PUBLIKA, 2025)
The quality of education is greatly influenced by the principal's managerial capacity, which is determined by the ability to effectively direct, manage, and evaluate all school activities. This study aims to analyze the influence of the Teacher Activity Center (PKG) and Teacher Performance Assessment on the Principal's Managerial Capacity, with Teacher Professional Competence as an intervening variable. The study was conducted at SMAN 1 Syiah Utama, Bener Meriah Regency, using a quantitative approach with a saturated sample of 63 teachers. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that PKG had a positive but insignificant effect on the principal's managerial capacity, but a positive and significant effect on teacher professional competence. Teacher performance assessment was proven to have a positive and significant effect on both the principal's professional competence and managerial capacity. In addition, teacher professional competence also had a significant effect on managerial capacity, and mediated the relationship between PKG and teacher performance assessment on the principal's managerial capacity. These findings emphasize the importance of strengthening teacher professional competence through systematic performance development and evaluation programs in supporting effective managerial leadership.